Cultural History of Humor: provisional balance and research perspectives - Saliba, Elias Thomé (2017)
The article aims to synthesize the most recent contributions of the various researches in the interdisciplinary area of the studies of humor, taking them as starting points to discuss methodological issues inherent in a cultural history of humor. It presents a summary of the researches on the humorous universe realized in the areas of neurology, cognitive sciences, primatology, its efforts and limitations in the definition of a field of studies regarding the subject. It also discusses the main formal theories of humor, pointing out redundancies but also possible heuristic indications and thematic guidelines for the humor historian. In the context of the linguistic and subjective lines that have given epistemological dilemmas to the humanities, it also presents some examples of important publications on the cultural history of humor, suggestions from various fields of research and sources and, in general, how this field of studies can forge new grades of understanding of history.